2023
DOI: 10.1002/jsp2.1287
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical crosstalk between the intervertebral disc, facet joints, and vertebral endplate following acute disc injury in a rabbit model

Matthew Fainor,
Brianna S. Orozco,
Victoria G. Muir
et al.

Abstract: BackgroundVertebral endplate sclerosis and facet osteoarthritis have been documented in animals and humans. However, it is unclear how these adjacent pathologies engage in crosstalk with the intervertebral disc. This study sought to elucidate this crosstalk by assessing each compartment individually in response to acute disc injury.MethodsEleven New Zealand White rabbits underwent annular disc puncture using a 16G or 21G needle. At 4 and 10 weeks, individual compartments of the motion segment were analyzed. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…Using a rabbit model, Fainor et al show that perturbations in disc biomechanics not only cause local pathological remodeling in structures such as the vertebral endplates, but also in adjacent structures such as the facet joints. 2 Easson et al identified the ion channel transient receptor potential vanilloid 4 (TRPV4) as performing a critical role in mediating the interplay between inflammation and loading in mouse intervertebral discs. 3…”
Section: Special Issue Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a rabbit model, Fainor et al show that perturbations in disc biomechanics not only cause local pathological remodeling in structures such as the vertebral endplates, but also in adjacent structures such as the facet joints. 2 Easson et al identified the ion channel transient receptor potential vanilloid 4 (TRPV4) as performing a critical role in mediating the interplay between inflammation and loading in mouse intervertebral discs. 3…”
Section: Special Issue Highlightsmentioning
confidence: 99%
“…show that perturbations in disc biomechanics not only cause local pathological remodeling in structures such as the vertebral endplates, but also in adjacent structures such as the facet joints. 2 Easson et al…”
mentioning
confidence: 99%
“…The IVD comprises three distinct tissue structures: the fibrocartilage ring, termed the annulus fibrosis, that encloses the central gelatinous nucleus pulposus 2 of 16 (NP) tissue, and two cartilaginous endplates where the disc borders the vertebrae. Agerelated disc degeneration is a progressive condition that may impair the stability of the spinal column, giving rise to a variety of spinal disorders [3,4]. This degenerative process of irreversible change is marked by a decline and deterioration in NP cells, resulting in changes in the extracellular matrix (ECM) composition, thereby compromising the disc's biomechanical features [3,5].…”
Section: Introductionmentioning
confidence: 99%